Kemampuan Biofiltrasi Aerob dalam Menurunkan Beban Organik Limbah Cair Soaking Kulit Sapi - Maurennisha Saskia; Tuhu Agung (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This research used cowhide soaking liquid waste in the home industry for washing cow culture in North Surabaya and then analyzed it on a laboratory scale using an aerobic biofilter with variations in the porosity of the media chamber and residence time (td) in the bioballs to remove COD, TSS and NH3-N parameters. Sampling point of wastewater was taken using purposive sampling method. The purpose of this research was to determine the effectiveness of aerobic biofilters in reducing pollutant parameters in cowhide soaking waste according to spatial porosity of 20,40,60% and residence time (td) of 12, 24, 36, 48, 60 hours. So that the research results obtained percent removal at 60% porosity media can reduce COD by 90%, TSS by 89%, and NH3-N by 89%. But the NH3-N parameter according to East Java Governor Regulation No. 52 of 2014 has not met the quality standard. Then for the most optimal residence time in removing COD, TSS and NH3-N is 60 hours, it can degrade COD by 89.98%, TSS by 86% and 88.51%.